The application of computednanotomography in biomedical sciencesand medicine: Uporaba nanotomografijev biomedicinski znanosti in medicini - Vajda, Jernej; Milojević, Marko; Maver, Uroš; Vihar, Boštjan (Acta Medico-Biotechnica, 2025)
Background: Computed nanotomography (nano-CT) is a cutting-edge imaging technology that provides ultra-high-resolution three-dimensional (3D) visualization at the cellular and subcellular levels, significantly surpassing conventional computed tomography (CT) and other imaging modalities. In this review, we describe the technological development of nano-CT along with its current capabilities and potential for integration into clinical medicine.Methods: We reviewed the existing literature relating to nano-CT technology, emphasizing biomedical research applications and evaluating potential for future clinical integration.Results: Nano-CT has demonstrated exceptional utility across various biomedical disciplines, including cardiology, vascular medicine, neurology, pulmonology, oncology and dentistry. This imaging technique provides unprecedented insights into tissue architecture, cellular details and pathological processes, providing significant enhancement in our understanding of diseases and supporting advancements in diagnosis, treatment planning, and therapeutic strategies.Conclusions: Despite remarkable potential for biomedical research, the clinical adoption of nano-CT faces several challenges, including limitations in imaging speed, soft tissue contrast, radiation dose and sample size. Continued technological innovations, clinical validation, and the development of multimodal imaging approaches are essential for the successful transition of nano-CT into routine medical diagnostics and personalized medicine.
Keywords: Computed tomography; CT; Microtomography; Micro-CT; Nanotomography; Nano-CT; Biomedical imaging